Information and Communication Technologies in Education as a Factor of Students Motivation - Kruchinina, Galina A.; Tararina, Larisa I.; Sokolova, Elena E.; Limarova, Elizaveta V.; Muskhanova, Isita V.; Arsaliyev, Shavadi M.; Bazayeva, Fatima U.; Tagirova, Nataliya P. (International Review of Management and Marketing, 2016)
The increased application of funds and information and communications technologies in vocational education has significantly changed the joint activities and communication between teachers and students. The objective of the article is to reveal the potential of information and communication technologies in education as a means of the students’ development. The authors have studied the peculiarities of motivation development by means of modern information technology which contributes to the thorough selection of the teaching forms, methods and techniques. The results of the experiment on students’ motivation in the process of achieving legal competence with the help of information and communication technologies are submitted. Through diagnostic tools 300 students were evaluated and the importance of information and communications technology in the formation of university students’ motivation to learn was proved. The article is devoted for teachers and researchers engaged in the implementation of co-temporary teaching methods in the educational process of the university. Keywords: Higher Education, Learning Motivation, Information and Communication Technology, Development. JEL Classifications: A23, I23, I26